Neutral Complexes of Alkali Metals with Picolinic Acid N-Oxide and Quinaldinic Acid N-Oxide - Prakash, D.; Sinha, K.B.; Gupta, O.P.; Shukla, R.N. (Asian Journal of Chemistry, 2010)
Neutral complexes of alkali metals, belonging to ML · HL type, where M = K, Rb or Cs and HL = picolinic acid N-oxide and quinaldinic acid N-oxide have been synthesised and characterised by elemental analysis, conductance and infrared spectral studies.